High-intensity virtual-reality arm plus FES-leg interval training in individuals with spinal cord injury - Hasnan, N.; Julia, P.E.; Husain, R.; Davis, G.M. (De Gruyter, 2013)
This study investigated the effect of high-intensity arm and FES-leg cycle training in a virtual reality environment on power output, aerobic fitness and blood biochemistry in persons with spinal cord injury (SCI). Eight individuals with chronic SCI undertook 6 weeks of high-intensity (80-90 HRpeak) interval training using an arm+FES-leg tricycle. As a result of the virtual reality interval training program, subjects increased their peak aerobic fitness by 20 (p<0.05). Their body mass-adjusted VO2 peak also significantly increased from 19.3 +/- 3.4 mL.kg(-1).min(-1) to from 23.2 +/- 3.4 mL.kg(-1).min(-1). Arm+ leg peak power output during "hybrid" exercise was raised from 52.5 +/- 10.4 W to 70 +/- 12.0 W (P<0.05). Total cholesterol, HDL, LDL and oral glucose tolerance results were unchanged after training.